Colorectal cancer survival in patients without curative measures: a retrospective cohort study - Saini, Aman; Adeyeye, Ademola; Gao, Hao; Steele, Molly; Jafri, Alisha; Ruparelia, Pranay; Manchukonda, Bhavya; Haji, Amyn (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: A substantial proportion of colorectal cancer (CRC) patients are managed without curative intent due to frailty, comorbidity, or patient choice. Outcomes in this heterogeneous population remain incompletely characterised. We evaluated survival and treatment patterns in patients managed non-curatively, including exploratory analyses by tumour sidedness and metastatic status.Methods: We conducted a retrospective cohort study of patients diagnosed with CRC at King’s College Hospital, London, between 2013 and 2022. Patients with histologically or radiologically confirmed CRC discussed at the multidisciplinary team (MDT) meeting were included; those receiving curative-intent treatment were excluded. Baseline variables included Eastern Cooperative Oncology Group (ECOG) performance status, tumour location, and metastatic disease at diagnosis. Overall survival (OS) from diagnosis was analysed using Kaplan-Meier methods and multivariable Cox regression.Results: Of 1,501 patients with CRC, 267 (18%) were managed non-curatively. Mean age was 74.7 years, and 60.3% were male; 59.9% were ECOG 0–2. Chemotherapy (28%) and surgery (15.7%) were the most frequent treatments. 5.2% required emergency surgery. Median OS was 210 days [95% confidence interval (CI): 205–210]. On multivariable analysis, ECOG ≥3 [hazard ratio (HR) 2.40, 95% CI: 1.42–4.05; P=0.001] and metastatic disease (HR 2.36, 95% CI: 1.41–3.94; P=0.001) were independently associated with worse OS. Tumour sidedness was not associated with survival (HR 1.00, 95% CI: 0.62–1.61; P=0.99).Conclusions: Patients with CRC managed non-curatively are often ambulant and may continue to receive supportive interventions aimed at maintaining quality of life. These findings support individualised risk stratification and prospective evaluation incorporating frailty and quality-of-life measures.